Chemical Structure of TiO2 Nanotube Photocatalysts Promoted by Copper and Iron. (22nd June 2013) - Liao, Chang-Yu; Wang, H. Paul; Lin, Hong-Ping
Abstract : TiO2 nanotubes (TNTs) promoted by copper (5%) (Cu-TNT) and iron (5%) (Fe-TNT) were prepared for visible-light photocatalysis. By X-ray absorption near edge structure (XANES) spectroscopy, it is found that the enhanced photocatalytic degradation of methylene blue (MB) on Cu-TNT and Fe-TNT is associated with the predominant surface photoactive sites A2 ((Ti=O)O4 ). By extended X-ray absorption fine structure (EXAFS) spectroscopy, the dispersed copper and iron also cause increases in the Ti–O and Ti–(O)–Ti bond distances by 0.01-0.02 and 0.04-0.05 Å, respectively. The decreased Ti–O bonding energy may lead to an increase of photoexcited electron transport. The copper- or-iron promoted TNT can thus enhance photocatalytic degradation of MB under the visible-light radiation.